Consumption Diagnosis of Sweet Cassava in three Municipalities in Cuba - Figueiredo, Priscila Gonzales [UNESP]; Bicudo, Silvio Jose [UNESP]; Valdivié, Manoel Isidoro; Mora, L. M.; Rodriguez, Bárbara (My University, 2014)
Cassava is an important staple food for human and animal feeding in Cuba. Despite its importance, there is little or nonexistent information to diagnose preferences and frequency of consumption of cassava in that country. In this sense, the present article characterizes the preferences and frequency of consumption of cassava in the municipalities of Plaza de la Revolución-La Habana province, El Salvador–Guantanamo province and San José de Las Lajas–Mayabeque province in Cuba. A survey was conducted through a questionnaire containing twelve closed and two open questions. The sample was determined based on the number of total population of each municipality considering 95% as confidence interval and 5% as error margin. The results were statistically analyzed by calculating the absolute and the relative frequencies of each question. It was observed that the acquisition of cassava in the municipalities of Plaza de la Revolución, El Salvador and San José de las Lajas in Cuba is done by purchase small quantities of fresh cassava for home consumption within one week, due to the extreme perishability of cassava, which limits consumers' ability to store fresh roots at home. The choice of cassava is made based on both skin colour (light brown) and pulp (white) and empirical knowledge about its ease of cooking, and that cassava is mostly consumed in boiled and fried forms up to four times a week in times where there is root market supply with the desirable culinary characteristics (cooking facility), that is, from September to December.
Keywords: Consumer preferences; Sweet cassava; La Habana; Mayabeque; Guantanamo